(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
This article provides information about the concept of tolerance and empathy, the ideas of tolerance, the development of a sense of tolerance, modern approaches to empathy, and the concept of the differentiation of the phenomenon of tolerance.